The Effectiveness Of Chain Card Game On Students’ Writing Skill : The Effectiveness Of Chain Card Game On Students’ Writing Skill - Siti masruhah - (JEET, Journal of English Education and Technology, 2021)
Some students find writing exercises boring, especially in English writing. So, one way to make students more motivated to write is to use games. One of the games is a chain card game. The subjects of this study were students of class VII B MTs Al-Ihsan. The results showed that the card game chain proved to be useful in learning to write English. From the results of the paired sample t test analysis shows that sig. the value is 0.000. Lower than the significance level (α) = 0.05 with degrees of freedom (df) = N-1 and the number of subjects (N) is 12 students. According to the value of sig. (2-tails) is 0.000. Given the basic concept of testing the hypothesis that if sig. (2-tailed) is smaller than (α) = 0.05, meaning that the hypothesis (H1) is accepted while the null hypothesis (H0) is rejected. Thus, it can be concluded that there is a significant effect of the Chain Card Game on the writing skills of the seventh-grade students of MTS al-ihsan